Functional chitosan nanofiber scaffold for osteochondral repair as well as preparation method and application of functional chitosan nanofiber scaffold

Through the functional shell polyanan nano -fiber bracket, using KGN and heparin modified shells shells of glycogen nano fiber to build a three -dimensional bracket with nano -microphone, solve the problems that the existing materials are difficult to meet the different needs of bones and cartilage, and realize bone cartilage. Effective repair of damage and differentiation of stem cells.

CN119326955APending Publication Date: 2025-01-21THE THIRD AFFILIATED HOSPITAL OF SOUTHERN MEDICAL UNIV (ACAD OF ORTHOPEDICS GUANGDONG PROVINCE)
0 Cites 0 Cited by

Patent Information

Application Number
CN202411243303.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-05
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

Existing osteocartilage repair materials are difficult to meet the different mechanical properties and microenvironmental needs of bone and cartilage at the same time, and there are problems such as easy separation of materials and poor cell survival status.

Method used

The functional shell polytanan nanofiber bracket is adopted, and the shell polycan nano -fiber has the function of promoting cartilage and osteicization through KGN modifiers and heparin modification.

Benefits of technology

A realization of osteochoconum repair microcysts, raising stem cells, promoting bone and cartilage differentiation of medium stem cells, repairing osteochoconia damage, and good biocompatibility and degradability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119326955A_ABST
    Figure CN119326955A_ABST
Patent Text Reader

Abstract

The invention relates to a functional chitosan nanofiber scaffold for osteochondral repair as well as a preparation method and application of the functional chitosan nanofiber scaffold. The functional chitosan nanofiber scaffold at least comprises a cartilage repair layer and a bone repair layer, the cartilage repair layer is composed of KGN modified chitosan nanofibers, and the bone repair layer is composed of a mineralized heparin modified chitosan nanofiber scaffold. The functionalized chitosan nanofiber scaffold has a three-dimensional porous structure, is degradable, can release functional active substances to promote the differentiation of mesenchymal stem cells to osteogenesis and chondrogenesis, and can be used for osteochondral injury repair.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of biomedical materials, in particular to a functionalized chitosan nanofiber scaffold for osteocartilage repair, and also to a preparation method of the scaffold and application thereof in osteocartilage repair. Background Art

[0002] Osteochondral injury refers to the damage of cartilage and subchondral bone. Cartilage is a highly specialized tissue that cannot regenerate spontaneously in the body once injured. The repair of osteochondral injury requires the simultaneous regeneration of cartilage and subchondral bone, which is very difficult to treat and has always been a problem in clinical practice. At present, the main clinical treatments for the repair and regeneration of osteochondral injury are microfracture and autologous osteochondral transplantation, but there are problems such as easy formation of fibrocartilage and limited donor sources. Tissue engineering provides a new approach for the treatment of osteochondral injury. Osteochondral scaffold materials gradually change from single layer to double layer and multilayer according to the different microenvironments and performance requirements of bone and cartilage tissue repair. The bone layer scaffold contains a large amount of inorganic components such as calcium phosphate, and the cartilage layer scaffold is mainly composed of extracellular matrix and does not require high mechanical properties. It is of great practical significance to construct an osteochondral composite scaffold according to the different structure and composition of osteochondral to achieve good repair of osteochondral.

[0003] The current construction methods of osteochondral repair grafts mainly include 3D printing technology and multilayer hydrogels. 3D printing technology can print different materials into scaffolds with ideal structures according to the needs of different levels, but when the bone layer and cartilage layer need materials of different properties for printing, the easy separation of the two phases is a difficult problem to solve. Hydrogel materials are mostly organic materials. After modification or doping with inorganic components to improve their mechanical strength, they can be used as the bone layer part of the hydrogel, but simple doping is difficult to present the nanostructure characteristics of inorganic materials. Cells cultured in hydrogels often only grow on the surface of the hydrogel. Tissue repair is that as the hydrogel degrades, new tissue gradually fills the defect; hydrogel scaffolds combined with 3D printing can make cells grow in, but the adhesion between its layers is insufficient; there are also related studies on direct loading of cells during the preparation of hydrogels. This method has strict requirements on preparation conditions, and the survival state of cells inside the hydrogel is not good. At present, no type of scaffold material has become a recognized ideal repair material in the field of osteochondral repair. Chitosan is similar to the glycosaminoglycan component of the extracellular matrix and is a good material for mimicking the extracellular matrix. However, the current electrospun chitosan nanofibers are relatively long and lack binding sites for constructing three-dimensional structures, making it difficult to prepare three-dimensional scaffolds.

[0004] Therefore, constructing a microenvironment that simulates osteochondral repair can recruit stem cells, promote the osteogenic and chondrogenic differentiation of mesenchymal stem cells, meet the different mechanical properties of bone and cartilage, and provide a multifunctional bioactive porous scaffold with a microenvironment to repair osteochondral damage, which has important clinical and social significance. Summary of the invention

[0005] One of the purposes of the present invention is to provide a functional chitosan nanofiber scaffold for osteochondral repair. The present invention uses chitosan nano short fibers as the main material, which are modified to have the functions of promoting cartilage differentiation and osteogenic differentiation, construct a chitosan nanofiber scaffold with a nano microenvironment, and recruit mesenchymal stem cells to promote osteogenic and chondrogenic differentiation to repair osteochondral damage.

[0006] To achieve the purpose of the present invention, the present invention adopts the following technical scheme: a functionalized chitosan nanofiber scaffold material for osteochondral repair, comprising at least a cartilage repair layer and a bone repair layer, wherein the cartilage repair layer is composed of chitosan nanofibers grafted with KGN, and the bone repair layer is composed of chitosan nanofibers modified by heparin and mineralized, that is, the cartilage repair layer is composed of KGN-modified chitosan nanofibers, and the bone repair layer is composed of a mineralized heparin-modified chitosan nanofiber scaffold.

[0007] The chitosan nanofibers used in the chitosan nanofibers of the present invention have a nanostructure similar to the natural extracellular matrix and exhibit positive charge when dispersed in water. Using them as scaffold materials can enable cells to grow in three-dimensional space and promote cell adhesion. After in vitro mineralization, the surface of the heparin-modified chitosan nanofibers can form uniform calcium phosphate nanosheets, forming an organic-inorganic composite structure with chitosan nanofibers as the skeleton and calcium phosphate nanosheets evenly distributed, constructing a bone layer microenvironment to promote the osteogenic differentiation of mesenchymal stem cells. After chitosan nanofibers are grafted with Kartogenin (2-([1,1-biphenyl]-4-ylaminoformyl)benzoic acid, KGN), they have the effect of promoting cartilage differentiation, and the degradation products are components of the extracellular matrix of cartilage cells. Functionalized chitosan nanofibers are endowed with the functions of promoting cartilage differentiation and osteogenic differentiation through modification and mineralization, constructing chitosan nanofiber scaffolds with nano-microenvironment, recruiting mesenchymal stem cells to promote osteogenic and chondrogenic differentiation to repair osteochondral damage.

[0008] Furthermore, there is an osteochondrium interface layer between the cartilage repair layer and the bone repair layer, which is composed of chitosan nanofibers with a high solid content. The unmodified chitosan nanofibers in the osteochondrium interface layer can better connect the cartilage layer and the bone layer scaffold, and play a barrier role to prevent the blood vessels in the bone layer from growing into the cartilage layer.

[0009] Each layer of the present invention adopts chitosan nanofiber as a matrix, and the layers are connected by physical entanglement between the nanofibers. During the experiment, the inventor found that chitosan nanofibers with a diameter of less than 5 μm and a length of less than 5 mm can achieve better results, while the chitosan nanofibers are too large, the connection between the layers is poor, and the stent is not well formed, and the diameter below 50 nm may produce cytotoxicity. Therefore, as an embodiment of the present invention, in the present invention, the chitosan nanofiber used is preferably a chitosan nanofiber with a diameter of less than 5 μm and a length of less than 5 mm, which can be obtained by chemical or mechanical treatment of chitosan fibers, or by chemical or mechanical treatment of chitosan powder.

[0010] Preferably, the chitosan nanofibers have a diameter of less than 1 μm and a length of less than 1 mm.

[0011] In the present invention, the mass ratio of KGN to chitosan nanofibers in the cartilage repair layer is 0.001 to 1. Preferably, the mass ratio of KGN to chitosan nanofibers in the cartilage repair layer is 0.01 to 0.1.

[0012] In the present invention, the mass ratio of heparin to chitosan nanofibers in the bone repair layer is 0.01 to 5. Preferably, the mass ratio of heparin to chitosan nanofibers in the bone repair layer is 0.1 to 2.

[0013] The second purpose of the present invention is to provide the application of the above functionalized chitosan nanofiber scaffold material.

[0014] Specifically, it involves the application of functionalized chitosan nanofiber scaffold as a scaffold for repairing bone cartilage.

[0015] The third object of the present invention is to provide a method for preparing the above-mentioned functionalized chitosan nanofiber scaffold.

[0016] Specifically, the preparation method of the functionalized chitosan nanofiber scaffold comprises the following steps:

[0017] (1) Preparation of KGN modified chitosan nanofibers: KGN, chitosan nanofibers and a coupling agent are mixed and subjected to coupling reaction to obtain a KGN modified chitosan nanofiber dispersion;

[0018] (2) Preparation of heparin-modified chitosan nanofiber scaffold: Heparin, chitosan nanofibers and a coupling agent are mixed and subjected to coupling reaction. After the reaction, unreacted substances are removed to prepare a heparin-modified chitosan nanofiber dispersion. A cross-linking agent is added and mixed to conduct a cross-linking reaction, freeze-formed, and dried to obtain a heparin-modified chitosan nanofiber scaffold;

[0019] (3) Mineralization of heparin-modified chitosan nanofibers: immersing the heparin-modified chitosan nanofiber scaffold in a mineralization solution for mineralization to obtain a mineralized heparin-modified chitosan nanofiber scaffold;

[0020] (4) A cross-linking agent is added to the KGN modified chitosan nanofiber dispersion and mixed evenly, and then injected into a mold, and then the mineralized heparin chitosan nanofiber scaffold is placed, allowed to stand, frozen, and dried to obtain the result.

[0021] In step (1), the mass ratio of KGN to chitosan nanofibers is 0.001 to 1, the reaction temperature is 5° C. to 40° C., the reaction is carried out under EDC / NHS catalytic conditions, and the reaction time is 12 hours to 48 hours.

[0022] Preferably, the mass ratio of KGN to chitosan nanofibers is 0.01-0.1, the reaction temperature is 25° C., and the reaction time is 24 hours.

[0023] In step (2), the mass ratio of heparin to chitosan nanofibers is 0.01 to 5, the reaction temperature is 5° C. to 40° C., the reaction is carried out under EDC / NHS catalytic conditions, and the reaction time is 12 hours to 48 hours.

[0024] Preferably, the mass ratio of heparin to chitosan nanofibers is 0.1-2, the reaction temperature is 25° C., and the reaction time is 24 hours.

[0025] EDC is 1-ethyl-(3-dimethylaminopropyl)carbodiimide and NHS is N-hydroxysuccinimide.

[0026] In the present invention, the chitosan nanofiber solid content of the KGN modified chitosan nanofiber dispersion of step (1) and the heparin modified chitosan nanofiber dispersion of step (2) is between 0.1wt% and 20wt%.

[0027] Preferably, the solid contents of the KGN modified chitosan nanofiber dispersion in step (1) and the heparin modified chitosan nanofiber dispersion in step (2) are 2 wt% to 5 wt% respectively, wherein the solid content of the heparin modified chitosan nanofiber dispersion is preferably 3.3 wt%.

[0028] In step (2), 0.01% to 10% by volume of a crosslinking agent is added to the heparin-modified chitosan nanofiber dispersion, and the crosslinking reaction is carried out at 10° C. to 90° C. for 4 to 48 hours, and then the dispersion is frozen in a refrigerator and dried to obtain a formed heparin-modified chitosan nanofiber scaffold.

[0029] Preferably, the crosslinking agent is glutaraldehyde, formaldehyde, or epichlorohydrin, etc. The amount of the crosslinking agent added is 0.1% of the total chitosan nanofiber dispersion, crosslinking is performed at 25° C. for 6 hours, and freezing is performed in a refrigerator for 12 hours.

[0030] In step (3), the heparin-modified chitosan nanofiber scaffold is immersed in a mineralizing solution for mineralization for 1 hour to 14 days, then washed with water for multiple times to remove unmineralized inorganic salts, and dried to obtain a mineralized heparin-modified chitosan nanofiber scaffold. Preferably, the mineralization time is 4 days and the drying temperature is 60°C.

[0031] The mineralizing liquid is a solution prepared from sodium chloride, sodium hydrogen phosphate, sodium bicarbonate, calcium chloride, magnesium chloride, etc.

[0032] When the scaffold has a bone cartilage interface layer, step (4) is: injecting KGN modified chitosan nanofiber dispersion into the mold, then injecting chitosan nanofiber dispersion, and then placing the formed mineralized heparin chitosan nanofiber scaffold, standing, freezing, and drying to obtain.

[0033] The solid content of the chitosan nanofiber dispersion is 5wt% to 10wt%.

[0034] In step (4), after standing at room temperature for 4 hours, the mixture is moved into a refrigerator and frozen for 12 hours, and the drying is freeze-drying.

[0035] The present invention has the following advantages:

[0036] 1. Compared with the existing osteochondral tissue engineering scaffold, the functionalized chitosan nanofiber scaffold provided by the present invention is a chitosan nano short fiber with a structure similar to that of the natural extracellular matrix (ECM), and its chemical structure is similar to the glycosaminoglycan in the cartilage component, and the nanofiber structure is conducive to the adhesion and aggregation of cells. After being modified by KGN, its degradation product has the effect of promoting the differentiation of mesenchymal stem cells into chondrogenic cartilage. The surface charge of the chitosan nanofiber modified by heparin becomes negatively charged, and calcium phosphate nanosheets can be formed on the surface of the chitosan nanofiber by immersion in a mineralizing solution, thereby simulating the bone tissue microenvironment and promoting the osteogenic differentiation of mesenchymal stem cells. The unmodified chitosan nanofiber in the osteochondrogenic interface layer can better connect the cartilage layer and the bone layer scaffold, and play a barrier role to prevent the bone layer blood vessels from growing into the cartilage layer. The nanofiber structure of the functionalized chitosan nanofiber scaffold material and the nano-microstructure of calcium phosphate can simulate the natural osteochondral microenvironment, and have many advantages such as inducing chondrogenic and osteogenic differentiation of mesenchymal stem cells, being degradable, similar to the natural ECM structure, and having good biocompatibility.

[0037] 2. After the functionalized chitosan nanofiber scaffold material provided by the present invention is implanted in the defect area, it will automatically swell and fill the entire defect area after absorbing blood. After the repair surgery using the functionalized chitosan nanofiber scaffold material, the joint can be flexed and extended in the early stage, but the affected limb needs to avoid weight bearing.

[0038] 3. The functionalized chitosan nanofiber scaffold provided by the present invention can absorb blood and body fluids to induce cell growth when implanted in the osteochondral defect. The material is non-immunogenic and degradable, and slowly releases effective ingredients that induce cartilage and osteogenesis to repair osteochondrocytes.

[0039] 4. The functionalized chitosan nanofiber scaffold material provided by the present invention improves the adhesion between the layers through the physical entanglement between the nanofibers and the interaction between the chemical crosslinking of the crosslinking agent and the hydrogen bonds, making it difficult to separate. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] Figure 1 This is a diagram of the structure of the functionalized chitosan nanofiber scaffold;

[0041] Among them, A is the physical picture and microstructure picture of the three-layer structure and double-layer structure of the chitosan nanofiber scaffold; the three-layer structure includes a cartilage repair layer (CSNF-KGN cartilage layer), an osteochondral interface layer (CSNF osteochondral interface layer), and a bone repair layer (CSNF-HP-M bone layer); the two-layer structure includes a cartilage repair layer (CSNF-KGN cartilage layer) and a bone repair layer (CSNF-HP-M bone layer);

[0042] B is the element distribution map of the mineralized area of ​​the bone repair layer and the unmineralized area of ​​the osteochondral interface layer.

[0043] Figure 2 Cell compatibility of each layer of functionalized chitosan nanofibrous osteochondral scaffold;

[0044] Figure 3 Animal surgery pictures of functionalized chitosan nanofibrous osteochondral scaffolds implanted into osteochondral defects in the knee joint. DETAILED DESCRIPTION

[0045] In order to further understand the present invention, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative work are within the scope of protection of the present invention.

[0046] Unless otherwise specified, the reagents involved in the embodiments of the present invention are all commercially available products and can be purchased through commercial channels.

[0047] In the following examples, the chitosan nanofibers used are all short fibers, i.e. chitosan fibers with a diameter of less than 5 μm and a length of less than 5 mm. Preferably, the chitosan nanofibers have a diameter of less than 1 μm and a length of less than 1 mm. They can be obtained by chemically or mechanically treating chitosan fibers, or by chemically or mechanically treating chitosan powders.

[0048] Example 1

[0049] KGN was dissolved and added into the chitosan nanofiber dispersion to make the mass ratio of KGN to chitosan nanofiber be 0.03:1. The mixture was reacted at 25°C for 24 hours under the catalysis of EDC / NHS to obtain a KGN modified chitosan nanofiber dispersion with a solid content of 3wt%.

[0050] The chitosan nanofiber dispersion is centrifuged to remove water, and then dispersed in water and stirred evenly to adjust the solid content to 5wt% as the bone cartilage interface layer fiber material.

[0051] Heparin was added to the chitosan nanofiber dispersion to make the mass ratio of heparin to chitosan nanofiber 0.7:1, and the reaction was carried out at 25°C for 24 hours under the catalysis of EDC / NHS to prepare heparin-modified chitosan nanofibers, and the unreacted heparin and excess water were removed by centrifugation and washing 3 times. The heparin-modified chitosan nanofibers were dispersed in water again to adjust the solid content to 3.3wt%, and the heparin-modified chitosan nanofiber dispersion was obtained. Epichlorohydrin with a volume ratio of 1% was added, and the fiber dispersion was transferred into a mold, cross-linked at room temperature for 6 hours, transferred to a -20°C refrigerator for 12 hours, and freeze-dried to obtain a heparin-modified chitosan nanofiber scaffold. The scaffold was immersed in the mineralization solution, and the mineralization solution was changed twice a day. After 4 days of mineralization, the scaffold was soaked and washed three times with deionized water, and the scaffold was placed in a 60°C oven for 24 hours to finally obtain a mineralized heparin-modified chitosan nanofiber scaffold.

[0052] The mineralizing liquid is a solution of sodium chloride, sodium hydrogen phosphate, sodium bicarbonate, calcium chloride or magnesium chloride.

[0053] 1% (v / v) epichlorohydrin was added to the KGN modified chitosan nanofiber dispersion and the chitosan nanofiber dispersion, respectively, and mixed thoroughly. The two were added to the mold in sequence, that is, the KGN modified chitosan nanofiber dispersion was injected first, then the chitosan nanofiber dispersion was injected, and finally the mineralized heparin modified chitosan nanofiber scaffold was placed. The cross-linking reaction was allowed to stand at room temperature for 4 hours, and then transferred to a -20°C refrigerator for freezing for 12 hours, and finally freeze-dried to obtain a functional chitosan nanofiber osteochondrocyte scaffold, such as Figure 1A three-layer scaffold. After the functionalized chitosan nanofiber scaffold was formed, the structure of the bone repair layer and the osteochondral interface layer was observed by scanning electron microscopy. The element distribution map clearly showed that the mineralized heparin-modified chitosan nanofiber scaffold in the bone repair layer containing calcium and phosphorus elements and the osteochondral interface layer without calcium and phosphorus (such as Figure 1 B), indicating that while the bone layer and the osteochondral interface layer are tightly connected, there are obvious differences in the composition and microstructure between the layers to adapt to the repair microenvironment of different parts of the osteochondral cartilage and promote the differentiation of mesenchymal stem cells in different directions.

[0054] Example 2

[0055] Different from Example 1, the functionalized chitosan nanofiber scaffold material is a double-layer structure consisting of a cartilage repair layer and a bone repair layer. Figure 1 The double-layer bracket in A.

[0056] During its preparation, 1% (v / v) epichlorohydrin is added to the KGN modified chitosan nanofiber dispersion and mixed thoroughly, injected into a mold, and then the mineralized heparin modified chitosan nanofiber scaffold is placed. The cross-linking reaction is allowed to stand at room temperature for 4 hours, then transferred to a -20°C refrigerator and frozen for 12 hours, and finally freeze-dried to obtain a functionalized chitosan nanofiber osteochondrocyte scaffold.

[0057] Example 3

[0058] According to the method of Example 1, KGN modified chitosan nanofiber scaffolds, chitosan nanofiber scaffolds, heparin modified chitosan nanofiber scaffolds and mineralized heparin modified chitosan nanofiber scaffolds were constructed respectively, and the four scaffolds were co-cultured with bone marrow mesenchymal stem cells for 24 hours, and the absorbance was measured by CCK-8 staining, indicating that each layer of the scaffold had good cell compatibility, such as Figure 2 .

[0059] Example 4

[0060] A 4 mm diameter osteochondral defect was made in the femoral trochlear region of the New Zealand rabbit knee joint, and a depth of 6 mm including the subchondral bone region. The functionalized chitosan nanofiber scaffold in Example 1 was implanted into the defect site, and the scaffold can absorb blood and body fluids to perfectly fill the defect site (such as Figure 3 ), close the wound and allow free movement after surgery.

[0061] Example 5

[0062] The difference from Example 1 is:

[0063] KGN was dissolved and added into the chitosan nanofiber dispersion to make the mass ratio of KGN to chitosan nanofiber be 0.01:1. The mixture was reacted at 25°C for 36 hours under the catalysis of EDC / NHS to obtain a KGN-modified chitosan nanofiber dispersion with a solid content of 5wt%.

[0064] The chitosan nanofiber dispersion is centrifuged to remove water, and then dispersed in water and stirred evenly to adjust the solid content to 8wt% as the bone cartilage interface layer fiber material.

[0065] Heparin was added to the chitosan nanofiber dispersion to make the mass ratio of heparin to chitosan nanofiber 1:1, and the reaction was carried out at 25°C for 36 hours under the catalysis of EDC / NHS to prepare heparin-modified chitosan nanofibers, and the unreacted heparin and excess water were removed by centrifugation and washing 3 times. The heparin-modified chitosan nanofibers were dispersed in water again to adjust the solid content to 3wt%, and the heparin-modified chitosan nanofiber dispersion was obtained. Epichlorohydrin with a volume ratio of 1% was added, and the fiber dispersion was transferred into a mold, cross-linked at room temperature for 6 hours, transferred to a -20°C refrigerator for 12 hours, and freeze-dried to obtain a heparin-modified chitosan nanofiber scaffold. The scaffold was immersed in the mineralization solution, and the mineralization solution was changed twice a day. After 4 days of mineralization, the scaffold was soaked and washed three times with deionized water, and the scaffold was placed in a 60°C oven for 24 hours to finally obtain a mineralized heparin-modified chitosan nanofiber scaffold.

[0066] Example 6

[0067] The difference from Example 1 is:

[0068] KGN was dissolved and added into the chitosan nanofiber dispersion to make the mass ratio of KGN to chitosan nanofiber be 1:1, and reacted at 25°C for 12 hours under the catalysis of EDC / NHS to obtain a KGN modified chitosan nanofiber dispersion with a solid content of 2wt%.

[0069] The chitosan nanofiber dispersion is centrifuged to remove water, and then dispersed in water and stirred evenly to adjust the solid content to 10wt% as the bone cartilage interface layer fiber material.

[0070] Heparin was added to the chitosan nanofiber dispersion to make the mass ratio of heparin to chitosan nanofiber 1:1, and the reaction was carried out at 25°C for 36 hours under the catalysis of EDC / NHS to prepare heparin-modified chitosan nanofibers, and the unreacted heparin and excess water were removed by centrifugation and washing 3 times. The heparin-modified chitosan nanofibers were dispersed in water again to adjust the solid content to 5wt%, and the heparin-modified chitosan nanofiber dispersion was obtained. Epichlorohydrin with a volume ratio of 1% was added, and the fiber dispersion was transferred into a mold, cross-linked at room temperature for 6 hours, transferred to a -20°C refrigerator for freezing for 12 hours, and freeze-dried to obtain a heparin-modified chitosan nanofiber scaffold. The scaffold was immersed in the mineralization solution, and the mineralization solution was changed twice a day. After 4 days of mineralization, the scaffold was soaked and washed three times with deionized water, and the scaffold was placed in a 60°C oven for drying for 24 hours to finally obtain a mineralized heparin-modified chitosan nanofiber scaffold.

[0071] Those skilled in the art can refer to the content of this article and appropriately improve the process parameters. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art and are considered to be included in the present invention. The method and product of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

Claims

1. A functionalized chitosan nanofiber scaffold for osteochondral repair, characterized in that: It at least comprises a cartilage repair layer and a bone repair layer, wherein the cartilage repair layer is composed of KGN modified chitosan nanofibers, and the bone repair layer is composed of mineralized heparin modified chitosan nanofiber scaffolds.

2. The functionalized chitosan nanofiber scaffold according to claim 1, characterized in that: There is a bone cartilage interface layer between the cartilage repair layer and the bone repair layer, which is composed of chitosan nanofibers.

3. The functionalized chitosan nanofiber scaffold according to claim 1 or 2, characterized in that: The chitosan nanofiber has a diameter of less than 5 μm and a length of less than 5 mm.

4. The functionalized chitosan nanofiber scaffold according to claim 1, characterized in that: The mass ratio of KGN to chitosan nanofiber in the KGN modified chitosan nanofiber is 0.001-1; the mass ratio of heparin to chitosan nanofiber in the mineralized heparin modified chitosan nanofiber scaffold is 0.01-5.

5. Use of the functionalized chitosan nanofiber scaffold according to any one of claims 1 to 4 as a scaffold for repairing bone cartilage.

6. The method for preparing the functionalized chitosan nanofiber scaffold according to claim 1, characterized in that: The following steps are involved: (1) Preparation of KGN modified chitosan nanofibers: KGN, chitosan nanofibers and a coupling agent are mixed and subjected to coupling reaction to obtain a KGN modified chitosan nanofiber dispersion; (2) Preparation of heparin-modified chitosan nanofiber scaffold: Heparin, chitosan nanofibers and a coupling agent are mixed and subjected to coupling reaction. After the reaction, unreacted substances are removed to prepare a heparin-modified chitosan nanofiber dispersion. A cross-linking agent is added and mixed to conduct a cross-linking reaction, freeze-formed, and dried to obtain a heparin-modified chitosan nanofiber scaffold; (3) Mineralization of heparin-modified chitosan nanofibers: immersing the heparin-modified chitosan nanofiber scaffold in a mineralization solution for mineralization to obtain a mineralized heparin-modified chitosan nanofiber scaffold; (4) Add a crosslinking agent to the KGN modified chitosan nanofiber dispersion and mix well, inject into a mold, and then place the mineralized heparin chitosan nanofiber scaffold, let stand, freeze, and dry to obtain the product.

7. The method for preparing the functionalized chitosan nanofiber osteochondrocyte scaffold according to claim 6, characterized in that: In the step (1), the mass ratio of KGN to chitosan nanofibers is 0.001 to 1, the reaction temperature is 5°C to 40°C, the reaction is carried out under EDC / NHS catalytic conditions, and the reaction time is 12 hours to 48 hours; In the step (2), the mass ratio of heparin to chitosan nanofibers is 0.01 to 5, the reaction temperature is 5° C. to 40° C., the reaction is carried out under EDC / NHS catalytic conditions, and the reaction time is 12 hours to 48 hours.

8. The method for preparing the functionalized chitosan nanofiber osteochondrocyte scaffold according to claim 6, characterized in that: The chitosan nanofiber solid content of the KGN modified chitosan nanofiber dispersion of step (1) and the heparin modified chitosan nanofiber dispersion of step (2) is between 0.1wt% and 20wt%.

9. The method for preparing the functionalized chitosan nanofiber osteochondrocyte scaffold according to claim 6, characterized in that: In the step (2), a cross-linking agent with a volume ratio of 0.01% to 10% is added to the heparin-modified chitosan nanofiber dispersion, and a cross-linking reaction is carried out at 10° C. to 90° C. for 4 hours to 48 hours, and then the mixture is frozen in a refrigerator and dried to obtain a formed heparin-modified chitosan nanofiber scaffold; In the step (3), the heparin-modified chitosan nanofiber scaffold is immersed in a mineralizing solution for mineralization for 1 hour to 14 days.

10. The method for preparing the functionalized chitosan nanofiber bone cartilage scaffold according to claim 6, characterized in that: When the scaffold has a bone cartilage interface layer, the step (4) is: injecting a KGN modified chitosan nanofiber dispersion mixed with a crosslinking agent into the mold, then injecting a chitosan nanofiber dispersion mixed with a crosslinking agent, and then placing the mineralized heparin chitosan nanofiber scaffold, standing, freezing, and drying to obtain the product.